LITERATURE STUDY OF THE BENEFITS OF ROSELLA PETALS (Hibiscus sabdariffa L.) AS ANTIHYPERTENSION - Kirwanto, Ag.; Indarto; Suhendriyo; EP, Sari (Jurnal Jamu Kusuma, 2024)
Roselle (Hibiscus sabdariffa L.) has various benefits as antihypertensive, antifungal, anti-inflammatory, antidiabetic, antioxidant and antibacterial. This research aims to determine the benefits of roselle petals as an antihypertensive using a literature study method with data sources obtained from a data base. Searches for scientific articles were carried out on databases, namely Google Scholar, Semantic Scholar and Research Gate using the keywords "Rosella petals as antihypertensive", "Rosella as antihypertensive", "Rosella petals", "Hibiscus sabdarifa L.", "Antihypertensive" and "Antihypertensive ”. From the results of data searches from the three data bases published in 2018-2023, screening was carried out through titles and abstracts as well as inclusion and exclusion criteria, resulting in 12 articles which were final analyzed. Based on the review that has been carried out, the results show that roselle petals contain anthocyanin and quercetin compounds which are included in the flavonoid group to reduce blood pressure which works through a mechanism that inhibits inflammation, leading to vasodilation which causes increased blood pressure and functions as an ACE inhibitor. Roselle petals are also useful in lowering the pulse rate, as antioxidants and neoroprotective properties. Based on the results obtained, it can be concluded that roselle petals are useful as antihypertensives